Victory is its own reward: oxytocin increases costly competitive behavior in schizophrenia. Issue 4 (4th March 2020) - Bradley, Ellen R.; Brustkern, Johanna; De Coster, Lize; van den Bos, Wouter; McClure, Samuel M.; Seitz, Alison; Woolley, Joshua D.
Abstract: Background: Aberrant sensitivity to social reward may be an important contributor to abnormal social behavior that is a core feature of schizophrenia. The neuropeptide oxytocin impacts the salience of social information across species, but its effect on social reward in schizophrenia is unknown. Methods: We used a competitive economic game and computational modeling to examine behavioral dynamics and oxytocin effects on sensitivity to social reward among 39 men with schizophrenia and 54 matched healthy controls. In a randomized, double-blind study, participants received one dose of oxytocin (40 IU) or placebo and completed a 35-trial Auction Game that quantifies preferences for monetary v. social reward. We analyzed bidding behavior using multilevel linear mixed models and reinforcement learning models. Results: Bidding was motivated by preferences for both monetary and social reward in both groups, but bidding dynamics differed: patients initially overbid less compared to controls, and across trials, controls decreased their bids while patients did not. Oxytocin administration was associated with sustained overbidding across trials, particularly in patients. This drug effect was driven by a stronger preference for winning the auction, regardless of monetary consequences. Learning rate and response variability did not differ between groups or drug condition, suggesting that differences in bidding derive primarily from differences in the subjective value of social rewards. Conclusions: Our findings suggest that schizophrenia is associated with diminished motivation for social reward that may be increased by oxytocin administration.